2014
DOI: 10.3844/ajptsp.2014.132.138
|View full text |Cite
|
Sign up to set email alerts
|

Anticonvulsant and Neurotoxicity Evaluation of Some Newly Synthesized Thiazolyl Coumarin Derivatives

Abstract: The present series of compounds were synthesized with the aim to develop newer anticonvulsant agents that are comparatively more efficacious and safer than the currently used anticonvulsant agents. Various thiazolyl coumarins were synthesized by the reaction of 3-(bromoacetyl)-2H-chromen-2-one with different substituted aryl thiourea. The structures of the synthesized compounds were confirmed by spectral data and elemental analyses. Compounds were tested for anticonvulsant activity utilizing Pen Tylenetetra Zo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Also, author reported the sizes of the group also played an important role as the derivatives substituted with -fluoro group were most active followed by -chloro and -nitro. 77 Batra et al studied a series coumarin-carbohydrazides and their corresponding thiazolidinone derivatives on the basis of pharmacophoric distance mapping study and evaluated for neurotoxicity by rotorod test, anticonvulsant activity by MES animal model of seizures. Compounds (28) and (29) showed considerable protection against seizures and considered as the prototype molecules of the series, and their ED 50 values were found to be lesser than 150 μmol/ kg.…”
Section: Synthetic Coumarin Derivatives With Antiepileptic/anticonvul...mentioning
confidence: 99%
“…Also, author reported the sizes of the group also played an important role as the derivatives substituted with -fluoro group were most active followed by -chloro and -nitro. 77 Batra et al studied a series coumarin-carbohydrazides and their corresponding thiazolidinone derivatives on the basis of pharmacophoric distance mapping study and evaluated for neurotoxicity by rotorod test, anticonvulsant activity by MES animal model of seizures. Compounds (28) and (29) showed considerable protection against seizures and considered as the prototype molecules of the series, and their ED 50 values were found to be lesser than 150 μmol/ kg.…”
Section: Synthetic Coumarin Derivatives With Antiepileptic/anticonvul...mentioning
confidence: 99%
“…Coumarin-thiazole compounds have many activities such as antibacterial, antioxidant, anticonvulsive, anticancer, and for treating hypertension. [17][18][19][20][21] Combining multiple active molecules within the same structure is an important means to synthesize new substances, and it is also the main way to find compounds with new biological and physiological activities. Based on the above analysis, we have designed and synthesized a series of novel glycosyl coumarylthiazole derivatives in order to find new and effective AChE inhibitors.…”
Section: Synthesis and Anti-acetylcholinesterase Activities Of Novel mentioning
confidence: 99%
“…Coumarinthiazole compounds have many activities such as antibacterial, antioxidant, anticonvulsive, anticancer, and for treating hypertension. [17][18][19][20][21] Combining multiple active molecules…”
Section: Introductionmentioning
confidence: 99%
“…But these drugs may cause side effects like skin rashes, poor coordination, tiredness, fatigue, dizziness, short memory, confusion etc [20]. These undesirable side effects necessities need of development of new anticonvulsant derivatives [21]. After review of literature, Coumarin has shown potential in different biological activities and can open new arena for the development of new substituted derivatives.…”
Section: Introductionmentioning
confidence: 99%